(untitled) (International journal of artificial intelligence, 2024)
Nowadays it is ordinary case to encounter literary works with fathers as a vital hero. However it is tough to meet one in which the role of father has been revealed as well as in Jane Austen’s novels. In this article the concept of “father” and the role of “father in the novels of Jane Austen were discussed.